Sytuacja dziecka rodziców z zaburzeniami psychicznymi - Kubiak, Hanna (Pedagogika Społeczna Nova, 2024)
The text concerns the situation of children brought up by parents with mental disorders. It is estimated that about 1/5–1/4 of children’s population experiences such a burden. Problems affecting children from the above-mentioned group may concern various spheres of family life: attachment to parents, their involvement in school duties and spending time together, care for hygiene, health and order, relationships with extended family and friends, socio-economic context of development or participation in professional life, the benefits of which go beyond the question of material status. This text discusses selected developmental risk factors for children of parents with mental disorders. The factors were divided into categories: risk factors concerning: creating attachment with parents and emotional or social consequences related to the quality of these bonds, functioning in a wider social system, socio- economic situation of families, and finally factors related to parent’s hospitalization. The text describes the difficulties experienced by children of parents with mental disorders, but it is clear that the qualityof their lives depends on the combination of risk and protection factors, on the system of burdens and resources.